Soft-Tıssue Changes In Functıonal And Orthopeadıc Approach To Skeletal Class II Dıvısıon I Cases - Hakan Gögen; Ufuk Toygar Memikoğlu (Galenos Yayinevi, 1997)
The aim of the study was to evaluate the changes in the soft tissue profile with changes in the hard tissues in Class II patients treated by activator alone or occipital headgear+activator therapy. The material of this study consisted of lateral cephalometric films of 45 individuals. The individuals were divided into three groups of 15 each. First group of patients were treated by activator only, the second group of patients were treated by occcipital headgear+activator. Third group of patients receivedno orthodontic treatment and served as control. All individuals were similar in skeletal morphology, treatment/observation tinte and maturity periods. Statistical evaluation was done by utilizing paired t-test, variance analysis, duncan test and correlation analysis. According to the results, the Class II malocclusion originated front the lower jaw in all groups. The two treatment groups were similar in all aspects before treatment. The control group was similar to both treatment groups in terms of skeletal characteristics but there were some differences in dental parameters. The soft tissue in subnasal and symphisis region followed the hard tissues very closely during treatment in both treatment groups. In the lip région there were some differences. In both treatment groups the upper lip moved posteriorly according to the reference planes used to evaluate the soft tissue profile. Although the lower lip moved anteriorly in the activator group, it moved posteriorly in the occipital headgear+activator group. The intergroup difference was statistically significant. At the end of treatment, soft tissue profile improved in both treatment groups, it was coser to ideal in the occipital headgear+activator group.